2009
DOI: 10.1099/vir.0.009944-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a role for lysine residues in non-structural proteins 2 and 2/3 of the hepatitis C virus for their degradation and virus assembly

Abstract: It has been demonstrated that both uncleaved, enzymitically inactive NS2/3 and cleaved NS2 proteins are rapidly degraded upon expression in cells, phenomena described to be blocked by the addition of proteasome inhibitors. As this degradation and its regulation potentially constitute an important strategy of the hepatitis C virus (HCV) to regulate the levels of its non-structural proteins, we further investigated the turnover of these proteins in relevant RNA replication systems. A lysine-mutagenesis approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…NS2 has been implicated in virus particle assembly, although its precise role in this process is not understood (6,9,12,13,32,37,42,45). The W879 residue in NS2 is conserved in 100% of the genotype 2 and genotype 3 NS2 sequences listed in the Los Alamos HCV database.…”
Section: Discussionmentioning
confidence: 99%
“…NS2 has been implicated in virus particle assembly, although its precise role in this process is not understood (6,9,12,13,32,37,42,45). The W879 residue in NS2 is conserved in 100% of the genotype 2 and genotype 3 NS2 sequences listed in the Los Alamos HCV database.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous reports have indicated that NS2 is a relatively short-lived protein (t 1/2 of approximately 3 h [35,46]), mutations destabilizing NS2 could lead to diminished levels and loss of function and explain the observed decreased virus titers. While the D2A, Q8A, W35A, W36A, F77A, K81A, W82A, and L92A mutants did display lower viral protein levels (Fig.…”
Section: Initial Characterization Of the N-terminal Region Of Ns2 By mentioning
confidence: 99%
“…A number of cell culture-adaptive mutations and compensatory mutations that enhance or restore virus production have been mapped to the NS2 N-terminal region (9,28,(31)(32)(33)(34). Likewise, mutagenesis of select residues within the N-terminal domain has implicated the involvement of NS2 in the early steps of the assembly process (9,25,28,35,36). Sequence alignment of several HCV genotypes demonstrates high conservation in the protease domain (aa 94 to 217), and the crystal structure of this domain indicates that NS2 forms a dimer containing a composite active site analogous to those of cysteine proteases (37).…”
mentioning
confidence: 99%
“…Several cell culture-adaptive mutations that increase virus yields have been mapped to NS2 (16,21,25,60,76), and mutagenesis of NS2 identified several residues that are important for infectious virus production (10,23,55,71,77). We previously identified second-site mutations in E1 (A78T), E2 (I360T), NS3 (Q221L), and NS4A (E42G) that suppressed defects in virus particle assembly caused by specific NS2 mutations (55).…”
mentioning
confidence: 99%